Sediment carbon storage and related chemical properties of mangrove forest in Sarawak, Malaysia - Rambok, Empi (2013)
Mangrove forest is one of the fifth forest types found in Sarawak and its existence is beneficial for economic activities and ecology balancing. A study of a mangrove forests in sequestering carbon and related chemical soil properties was conducted at Wildlife Sanctuary Sibuti, Miri (WSSM) Mangrove Forest and Awat-Awat Lawas, Limbang (AALL) Mangrove Forest. The objectives of this study were to: (i) compare selected soil chemical properties of the two mangrove forests and (ii) compare their carbon storage with time. A total of 320 soil samples were collected from WSSM and AALL, 40 soil samples were collected from each study site for 4 sampling time. The first soil sampling were conducted in December 2009 (WSSM) and January 2010 (AALL), the second soil sampling was carried out in June 2010, the third soil sampling was conducted in August 2013, and the fourth sampling was carried out in October 2013. The first part of this study was to determine soil chemical properties of the mangrove forest in Sarawak. A contemporary mangrove soil condition is essential for addressing mangrove forest for carbon storage, and environmental balance. Mangrove soil samples were taken from Miri and Limbang Division of Sarawak at 0-30 cm depth in a 0.5 hectare plot. Selected soil chemical properties were determined and data obtained were analyzed using Statistical Analysis System (SAS) Version 9.2. Soil pH was determined using water and 1N KCl, soil organic matter and total carbon were analyzed using CHNS analyzer, total N was determined using Kjeldahl method, total P was determined using Aqua Regia method, cation exchange capacity was determined using leaching method, and humic acids were isolated using standard procedures. The soil acidity, total N, total P, CEC, and humic acid of both locations were significantly different except for total carbon and organic matter. Regional diversity has significant effects on the soil acidity, total N, total P, CEC and yield of humic acids of the study areas. Data obtained can be useful for further study on carbon stock and nutrients content. The second part of the study was to determine the potential of mangrove soil to store carbon and the soil condition between intervals of vegetation growth. This study examined the potential of the two mangrove forests soil to store carbon. Soil sampling was conducted in December 2009, January 2010, June 2010, August 2013, and October 2013, respectively, to study the effects of location and time. Soil carbon, soil organic matter, and stable carbon from humic acids were analyzed using CHNS analyzer. Bulk density was determined using coring method. Soil pH, total P, total N, CEC, and humic acids were determined as previously outlined. There were significant effects on soil total C at WSSM and AALL. The quantities of total C recorded at WSSM ranged from 29.50 Mg ha-1 (December 2009) to 90.16 Mg ha-1 (October 2013) while those of for AALL ranged from 38.94 to 48.49 Mg ha-1. The quantity of stable carbon in humic acids for WSSM in December 2009 was 1.34 Mg ha-1, June 2010 was 1.65 Mg ha-1, August 2013 was 1.69 Mg ha-1, and October 2013 was 1.12 Mg ha-1, For AALL; January 2010 was 1.95 Mg ha-1, June 2010 was 1.28 Mg ha-1, August 2013 was 0.56 Mg ha-1, and October 2013 was 0.48 Mg ha-1. The soil in both mangrove forests was acidic as pH values were as follows; (i) WSSM: 2.67 to 4.90 (in water) and 2.51 to 4.44 in pH (in KCl), and (ii) AALL: 2.44 to 3.73 (in water) and 2.40 to 3.68 (in KCl). The value of C:N ratios of the two sites were also very high ranging between 35.93 to 182.86. Based on comparison between WSSM and AALL, it was concluded that there were significant differences of soil pH in water and in KCl, total N and total P for first and second sampling. The soil at WSSM was more acidic than AALL and had higher amounts of soil organic matter, total N and total P. Soil of WSSM mangrove forest was better than AALL mangrove forest because when comparison was made between location during first soil sampling, WSSM showed higher content of organic matter, total C, total N, total P and cation exchange capacity. The significant difference of total soil C and stable C in humic acid were recorded at both study areas and comparison between times suggests that the mangrove soil has the potential to store carbon. However the ability of the mangroves to store C sediment depends on forest performance, the rate of decomposition, plant residue, locality, vegetation density and organic compounds.